Antiviral Drugs and Vaccines for Omicron Variant: A Focused Review - Nidhi Garg; Ananya Sree Kunamneni; Pankaj Garg; Sandeep Sharma; Divakar Sharma; Adinarayana Kunamneni (Canadian Journal of Infectious Diseases and Medical Microbiology, 2023)
The Omicron variant of concern (VOC) replaced the delta variant rapidly and became the predominant strain due to more mutations in spike protein and receptor-binding domain (RBD) enhancing its infectivity and binding affinity. The severity of the illness is less than that of the delta variant. Omicron is nonsusceptible to REGEN-COV™ and bamlanivimab with etesevimab. Drugs that are effective against the Omicron variant are oral antiviral drugs such as Paxlovid (nirmatrelvir/ritonavir), remdesivir, sotrovimab, and molnupiravir. The potency of sotrovimab is reduced to 3-fold against Omicron, and 8-fold reduction in potency with sotrovimab is found in a particular variant of Omicron with a R346K substitution in spike protein. There are neither clinical trials comparing the efficacy of these 4 therapies with each other nor any data on a combination of two or more therapies. The current recommendation for mild-moderate, nonhospitalized patients who are at a high risk of disease progression is to use Paxlovid as the first-line option. If Paxlovid is not available or cannot be administered due to drug interactions, then the next best choice is sotrovimab. The third choice is remdesivir if sotrovimab is also not available and molnupiravir is to be given if the other three options are not available or cannot be administered. For prevention, 2130 (cilgavimab) in combination with COV2-2196 (tixagevimab) has been effective against BA.2 only. LY-CoV1404 (bebtelovimab) is recently authorized as it is effective against all sublineages of the Omicron variant. Regarding vaccine efficacy (VE), the 3-dose VE with mRNA vaccines at 14–60 days was found to be 71.6%, and after 60 days, it is 47.4%. There is a 34–38-fold reduction of neutralizing activity with prebooster sera and a 19-fold reduction with booster sera for the Omicron variant. This probably explains the reason for worldwide breakthrough infections with the Omicron variant with waning immunity. The neutralizing antibody response against Omicron elicited by the bivalent vaccine is superior to that of the ancestral Wuhan strain, without any safety concerns. For future advances, the ribosome display technology can be applied for the generation of human single-chain fragment variable (scFv) antibodies from B cells of recovered patients against Omicron and other Coronavirus variants as they are easier and faster to produce and have high affinity and high specificity.